1990
DOI: 10.21236/ada233832
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Measures of Rifle Skills

Abstract: This paper addreises issues relatucl to the use of alternative and surrogate tests of the skills associated with rifle firing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Similarly, in another sample from the armed forces, Chung, O'Neil, Delacruz, and Bewley (2005) found a significant and moderate correlation between qualification and aptitude scores r = .34, p < .05 among 2nd lieutenants undergoing basic marksmanship training. These findings are consistent with prior studies examining the relation between various knowledge and aptitude measures and shooting performance (e.g., Boyce, 1987;Carey, 1990;Cline, Beals, & Seidman, 1960;MacCaslin & McGuigan, 1956;Thompson, Smith, Morey, & Osborne, 1980;Wisher, Sabol, Sukenik, & Kern, 1991).…”
Section: Rifle Marksmanship As a Complex Skillsupporting
confidence: 91%
“…Similarly, in another sample from the armed forces, Chung, O'Neil, Delacruz, and Bewley (2005) found a significant and moderate correlation between qualification and aptitude scores r = .34, p < .05 among 2nd lieutenants undergoing basic marksmanship training. These findings are consistent with prior studies examining the relation between various knowledge and aptitude measures and shooting performance (e.g., Boyce, 1987;Carey, 1990;Cline, Beals, & Seidman, 1960;MacCaslin & McGuigan, 1956;Thompson, Smith, Morey, & Osborne, 1980;Wisher, Sabol, Sukenik, & Kern, 1991).…”
Section: Rifle Marksmanship As a Complex Skillsupporting
confidence: 91%
“…Another important variable found to be related to shooting performance is experience with weapons and prior record-fire perfor- Rifle steadiness (Humphreys, Buxton, & Taylor, 1936) .72 43 Rifle steadiness (McGuigan & MacCaslin, 1955) .22 148 Rifle steadiness (Spaeth & Dunham, 1921) .61 73 Prior shooting experience and aptitude (MacCaslin & McGuigan, 1956) R = .67-.72 Prior shooting experience (Tierney, Cartner, & Thompson, 1979), males .24 Prior shooting experience (Tierney et al, 1979), females .19 Prior hunting experience (Tierney et al, 1979), males .21 Prior experience with a .22 rifle (Thompson, Smith, Morey, & Osborne, 1980), males .21-.25 Prior record-fire performance (McGuigan & MacCaslin, 1955), repeated qualification course 3 times .88, .84 Self-reported prior record-fire performance (Schendel, Morey, Granier, & Hall, 1983) .29 121 Prior record-fire performance (Smith, 2000, Experiment 2) .37 50 Prior record-fire performance (Thompson, Morey, Smith, & Osborne, 1981) 388 Weaponeer device-fire (Schendel et al, 1985, Experiment 1) .37-.74 102 Weaponeer device-fire (Schendel et al, 1985, Experiment 2) .17-.55 244 Combat Training Theater device-fire (Marcus & Hughes, 1979) Low Laser Marksmanship Training System device-fire (Smith & Hagman, 2000) .55 95 Laser Marksmanship Training System device-fire (Smith & Hagman, 2003, Study 1) .50 110 Laser Marksmanship Training System device-fire (Smith & Hagman, 2003, Study 2) .55 76 Engagement Skills Trainer device-fire (Hagman, 1998) .68 102 Other device-fire (Torre et al, 1987) .54 29 Cognitive ASVAB clerical/administrative (Carey, 1990) .26 a ASVAB general technician (Carey, 1990) .35 a ASVAB electrical repair (Carey, 1990) .32 a ASVAB mechanical maintenance (Carey, 1990) .38 a ASVAB composite (Carey, 1990) .32 a Infantry training GPA (Carey, 1990) .25 a Core job knowledge (Carey, 1990) .31 a Supervisor ratings (Carey, 1990) .16 a Skill Qualification Test, a measure of a soldier's skill achievement …”
Section: Perceptual-motor Variablesmentioning
confidence: 99%
“…Although not measures of marksmanship knowledge, these variables suggest the potential for shooters to acquire the knowledge. Carey (1990) examined the relation between a variety of background variables and first-term enlisted Marines' known distance record-fire performance. Moderate correlations between various subscales of the Armed Services Vocational Aptitude Battery (ASVAB) and record-fire scores were found, ranging from .26 for the Clerical/Administrative subscale to .38 on the Mechanical Maintenance subscale.…”
Section: Cognitive Variablesmentioning
confidence: 99%
“…As far as marksmanship training versus battlefield shooting skills are concerned, Carey (1990) found that the correlation between known distance (KD) scores and pop-up target scores was only 0.2. The pop-up target test more closely simulates actual battle conditions over KD scores.…”
Section: Simulators and Marksmanship Trainingmentioning
confidence: 99%